The effect of different inflated air insole in the foot plantar pressure - Fahni Haris; Shen Wei-Cheng; Wang Ji-Feng; Yori Pusparani; Ardha Ardea Prisilla; Lu Min-Wei; Liau Ben-Yi; Lung Chi-Wen (IJNP (Indonesian Journal of Nursing Practices), 2022)
Exercise promotes health in people with diabetes. Weight-bearing activities increase the risk of foot ulcers. Air-pressure shoes may relieve high plantar pressure. Nevertheless, no study has investigated whether air-pressure shoes affect the plantar foot. A repeated measures study design, with five healthy subjects were tested with three inner air pressures (80, 160, and 240 mmHg) and 20 minutes of walking to examine their effects on peak plantar pressure (PPP). PPP after walking was measured from the forefoot in the big toe (T1), first metatarsal head (M1), and second metatarsal head (M2). We used a one-way ANOVA to analyze the results. We found that after walking for 20 min, inner air pressure significantly affected plantar pressure in the M1 and M2 (P = 0.008 and 0.006, respectively). Regarding the inner air pressure effect, there was a significant difference in the M1 head between 80 and 240 mmHg (274.2 ± 35.6 kPa vs. 689.4 ± 106.3 kPa, P = 0.002) at 20 minutes of walking duration. Moreover, there was a significant difference in the M2 head between 80 mmHg and 240 mmHg (250.6 ± 30.1 kPa vs. 572.4 ± 87.3 kPa, P = 0.002) and 160 and 240 mmHg (396.6 ± 35.3.7 kPa vs. 572.4 ± 87.3 kPa, P = 0.050). This finding is significant because the higher inner air pressure shoes can increase plantar pressure compared to 80 mmHg inner air pressure. This study suggests that individuals who are at high risk of developing foot ulcers should wear shoes with an inner air insole (80 mmHg).